Cynara scolymus L. (Artichoke) - Botsaris, A. S. (2013)
Because of their antioxidant and free radical scavenging properties, extracts from artichoke have been used in folk medicine as hepatoprotective, in the treatment of cardiovascular diseases and in the inhibition of cholesterol biosynthesis. Flavonoids and polyphenols present in these extracts are responsible for such actions.